Crime Prevention - From the Imagination to the Reality (Kriminalističke teme, 2004)
This paper features the. basic crime prevntion program within th’ contemporary systems ofcrime policy or polititics of crime control. The. second part of the paper present diffemt model ofcrime prevention from the theoretical to the empirical level.The models elaborated in this paper lias been attempt to applay for a Bosnian circumstances especially relete to comunity crime prevention and community policing as a new model of policing in this area.